User Perceptions of Mobile Banking Apps in Tanzania: Impact of Information Systems (IS) Factors and Customer Personality Traits - Koloseni, Daniel Ntabagi (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2021)
This study probes the roles that information systems (IS) success factors and user personality traits play in Tanzanian users’ perceptions of their experiences with mobile banking apps. Based on a survey of 249 mobile banking customers, the study finds that users are being positively influenced by the apps’ system quality and system service, but not by the apps’ information quality. The study also finds that, with respect to user personality traits, openness, agreeableness, conscientiousness and extraversion are all traits that have a positive impact on customers’ use of, and satisfaction with, mobile banking apps. The findings suggest that developers of mobile banking apps for the Tanzanian market need to both improve the quality of the information in the apps and continue to target a range of personality traits.
Keywords: mobile banking apps, adoption, personality traits, information systems (IS), IS success model, Tanzania